-1.4-(0.2x+3)=0.8x-1.2

Simple and best practice solution for -1.4-(0.2x+3)=0.8x-1.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1.4-(0.2x+3)=0.8x-1.2 equation:


Simplifying
-1.4 + -1(0.2x + 3) = 0.8x + -1.2

Reorder the terms:
-1.4 + -1(3 + 0.2x) = 0.8x + -1.2
-1.4 + (3 * -1 + 0.2x * -1) = 0.8x + -1.2
-1.4 + (-3 + -0.2x) = 0.8x + -1.2

Combine like terms: -1.4 + -3 = -4.4
-4.4 + -0.2x = 0.8x + -1.2

Reorder the terms:
-4.4 + -0.2x = -1.2 + 0.8x

Solving
-4.4 + -0.2x = -1.2 + 0.8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.8x' to each side of the equation.
-4.4 + -0.2x + -0.8x = -1.2 + 0.8x + -0.8x

Combine like terms: -0.2x + -0.8x = -1x
-4.4 + -1x = -1.2 + 0.8x + -0.8x

Combine like terms: 0.8x + -0.8x = 0.0
-4.4 + -1x = -1.2 + 0.0
-4.4 + -1x = -1.2

Add '4.4' to each side of the equation.
-4.4 + 4.4 + -1x = -1.2 + 4.4

Combine like terms: -4.4 + 4.4 = 0.0
0.0 + -1x = -1.2 + 4.4
-1x = -1.2 + 4.4

Combine like terms: -1.2 + 4.4 = 3.2
-1x = 3.2

Divide each side by '-1'.
x = -3.2

Simplifying
x = -3.2

See similar equations:

| 4x^2+18x-1882=0 | | x+5+x-2=54-15 | | -5=x+10 | | x+5+x-2=54 | | 6(5x+4)+2(3x-7)-5(7x-4)= | | 5(2t+5)= | | x+(x*12.36/100)=450648.16 | | 3x^2+24x=0forx | | 3/4x+5/4-1/4 | | 21x+77-18x+54= | | 16^2/3 | | ln(3x^2)=8 | | N*18=126 | | -5+8-4(2y+1)= | | 18x+36+12x-21= | | 9/4x=6/2 | | 2x+15=5x+14 | | 0.7n=-77 | | 6-2b+3=1 | | 8y-13=-5(y-5) | | N/8=16 | | -5s-48=-a | | 3(4x-17)=3(x+7) | | 36x-45= | | -2(-7n+1)=5n-10 | | 46+21=11g | | 10-5m=45 | | 3(5y-5)-4= | | 17-11=2(x-7) | | 0.7t-3.2=1.7 | | h=-16t^2+60t+1 | | 7x+19-4x+4= |

Equations solver categories